Os ex-pobres do Brasil : as representações da “nova classe média” nas revistas carta capital, época, istoé e veja - Hansen , Cândida (2015)
The objective of this work is to analyze the representations of the so-called Brazil's new middle class on the magazines Veja, IstoÉ, Época and Carta Capital between the years 2008 and 2013. From the perspective of Cultural Studies and understanding of journalism as a producer of meanings in society, we attempt to make a cultural analysis of the object through the reflections especially of Hall (1999, 2003) and Benetti (2013). The so-called new middle class is discussed through the perspective of Neri (2011), Pochmann (2012) and Souza (2010). From crossing of theoretical references related to journalism and the new middle class, the research corpus, consisting of six reportages, is analyzed. We conclude that the so-called new middle class is represented by an economistic view (Souza, 2010, 2013), in which the income and consumption are the main factors to fit individuals into this group, at the expense of intangible values such as social and cultural capitals, essential for understanding the production and reproduction of classes over time.